Agriscience : fundamentals & applications - Cooper, Elmer L. (Albany, N.Y. : Delmar Publishers, 1990)
An agriscience textbook exploring such topics as environmental technology, plant sciences, integrated pest management, interior and exterior plantscape, animal sciences, food science, and agribusiness.
Includes index.
Keywords: Agriculture; Agriculture